Synergistic effects of Bi2O3 and Ta2O5 for efficient electrochemical production of H2O2 - Jiang, Chenghang; Fei, Yan-Fei; Xu, Weiwei; Bao, Zhikang; Shao, Yizhen; Zhang, Shijie; Hu, Zhong-Ting; Wang, Jianguo (Applied catalysis. B, Environmental, 2023)
Electrochemical oxygen reduction reaction (ORR) through a two-electron pathway has been provided a green route for on-site hydrogen peroxide (H2O2) production. Developing high-selective electrocatalysts for H2O2 production are urgently sought. Herein, a m-Bi2O3/Ta2O5 electrocatalyst (m: “Bi” mass contents) has been successfully synthesized by simple physical mixing associated with an outstanding selectivity towards H2O2 (94.7%), over 10% higher than Ta2O5 (80.9%) and Bi2O3 (81.7%). 10-Bi2O3/Ta2O5 also exhibits 471 mmol/(gcat·h) H2O2 yield with 91.8% Faraday Efficiency. The in-situ generated H2O2 can function as disinfection agent for efficiently deactivating model bacteria (e.g., Pseudomonas aeruginosa, Staphylococcus aureus and Escherichia coli) within 30 min. In-situ Raman and DFT proposed the synergistic effects of Bi2O3 and Ta2O5 in boosting 2e- ORR performance. In this work, it not only presents a high-selective electrocatalyst for 2e- ORR, but also provides a new idea for electrocatalyst design from the perspective of reaction process. [Display omitted] •Electrocatalytic H2O2 production of 10-Bi2O3/Ta2O5 reaches a 94.7% high selectivity.•Enhanced O2 adsorption and H2O dissociation of 10-Bi2O3/Ta2O5 results in efficient OOH formation.•10-Bi2O3/Ta2O5 exhibits excellent durability for 80 h at 0.4 VRHE.•Over 90% FE during H2O2 produce in homemade H-cell.•The applications of on-site production of low-concentration H2O2 in water disinfection.